Affective Ablenationalisms and Interspecies Entanglements - Todd, Anastasia (Disability Studies Quarterly, 2023)
In 2015, the news outlet Today posted a video interview with Chopper Maroshek, a former Navy Seal, about the “unbreakable bond” between himself and his service dog, a German Shepherd named Chopper. Before Chopper was Maroshek’s service dog, he was his multi-purpose canine partner, trained and deployed for combat in Iraq and Afghanistan. This article analyzes representations of Chopper and Maroshek in the Today video, its comment archive, and popular news articles to show how Chopper, in his role as a multi-purpose canine-cum-service dog, is hailed to participate in the project of ablenationalism. I argue that Chopper is constructed as an exceptional technology of rehabilitation, facilitating Maroshek’s ability to fold back into the nation as an “able-disabled” subject. Building on transnational disability and animal studies scholarship, I illuminate how the circulation of Maroshek and Chopper’s spectacular story justifies the uneven biopolitical inclusion of American veterans with mental and/or psychiatric disabilities, effectively obscuring the violent production of disability through war. Ultimately, I show how the nationalist affects that shape Chopper as the apotheosis of a service dog covertly sutures an ablenationalist politics of disability to a racialized U.S. biopolitics of war.